Effects of Budget, Project Delays, and Resource Procurement on Construction Project Performance Using SEM-PLS - Josua Riski Silaen; Pio Ranap Tua Naibaho (Universitas Medan Area, 2026)
Construction projects frequently encounter challenges related to budget management, project delays, and resource procurement, all of which may significantly influence project performance. This study aims to analyze the direct and indirect relationships among these factors using an integrated Statistical Package for the Social Sciences (SPSS) and Partial Least Squares Structural Equation Modeling (SEM-PLS) approach. A quantitative research design was employed using questionnaire data collected from 150 construction professionals representing contractors, consultants, project managers, supervisors, and engineers. IBM SPSS 26.0 was utilized for descriptive statistics, validity, reliability, normality, multicollinearity, and multiple regression analyses, while SmartPLS 4 was used to evaluate the structural model. The results demonstrate that budget management has the strongest direct effect on construction project performance (β = 0.796, p < 0.001). Resource procurement exhibits the greatest influence on budget management (β = 0.834, p = 0.001), whereas project delays significantly affect both budget management and project performance. Furthermore, the proposed structural model satisfies the goodness-of-fit criteria (SRMR = 0.045; NFI = 0.945), indicating an acceptable model fit. These findings highlight the importance of effective financial planning and resource management in improving construction project performance and provide empirical evidence for project managers in developing strategies to minimize delays and optimize project outcomes.